Fiscal consolidation by austerity and EU surveillance policies - Aurel Iancu; Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2015)
After a brief introduction dealing with critical opinions of some economists on the European austerity policy, the authors point out that austerity as a means of achieving fiscal consolidation and financial stability is applied when the fiscal domain is weak. After analyzing the effects of the 2009 crisis on some indicators and austerity measures taken by almost all EU countries, the study presents the content and the role of the EU fiscal compact and methodology used to support the fiscal consolidation measures. Most of the study consists in the analysis of the outcome of this methodology (through indicators, key-equations, graphs) revealing the relationships between indicators: effective GDP and potential GDP, production variation, effective, cyclical and structural deficits as well as the deficit in the balance of payments. The paper reveals some shortcomings of the new mechanism which affect the development of some major segments of the real economy, such as public investments, and further the economic potential growth on medium and long terms.
Keywords: E62; F02; H2; H5; H6; H7; 330; fiscal policy; budget deficits; structural deficits; austerity; fiscal consolidation; the golden rule of public finance; economic growth